2014
DOI: 10.1016/j.neuron.2014.01.038
|View full text |Cite
|
Sign up to set email alerts
|

A Transcription Factor Network Coordinates Attraction, Repulsion, and Adhesion Combinatorially to Control Motor Axon Pathway Selection

Abstract: SUMMARY Combinations of transcription factors (TFs) instruct precise wiring patterns in the developing nervous system; however, how these factors impinge on surface molecules that control guidance decisions is poorly understood. Using mRNA profiling, we identified the complement of membrane molecules regulated by the homeobox TF Even-skipped (Eve), the major determinant of dorsal motor neuron (dMN) identity in Drosophila. Combinatorial loss- and gain-of-function genetic analyses of Eve target genes indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Furthermore, the knockout of the ZEB orthologues, ZAG1 and Zfh1, result in defects in neuronal differentiation and in axonal growth in C. elegans and Drosophila, respectively (Clark and Chiu, 2003;Layden et al, 2006;Lee and Lundell, 2007;Ramakrishnan and Okkema, 2014;Vogler and Urban, 2008;Wacker et al, 2003;Zarin et al, 2014). Interestingly, Zeb1À/À mice, which die perinatally with numerous skeletal defects, do not display neural defects despite Zeb1 expression in the neural tube (Takagi et al, 1998), highlighting a unique role for Zeb2 in nervous system development.…”
Section: Zeb2 Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the knockout of the ZEB orthologues, ZAG1 and Zfh1, result in defects in neuronal differentiation and in axonal growth in C. elegans and Drosophila, respectively (Clark and Chiu, 2003;Layden et al, 2006;Lee and Lundell, 2007;Ramakrishnan and Okkema, 2014;Vogler and Urban, 2008;Wacker et al, 2003;Zarin et al, 2014). Interestingly, Zeb1À/À mice, which die perinatally with numerous skeletal defects, do not display neural defects despite Zeb1 expression in the neural tube (Takagi et al, 1998), highlighting a unique role for Zeb2 in nervous system development.…”
Section: Zeb2 Interactionmentioning
confidence: 99%
“…Zeb2 was shown to act cell-autonomously to direct cortical interneuronal migration through regulation of the precise levels of the Unc5b netrin-repulsive receptor, with Unc5b knockout also being shown to rescue the migration defect of the Zeb2 mutant mice . Conversely, the Drosophila ZEB orthologue, Zfh1, has been shown to positively regulate Unc5b expression in neurons (Zarin et al, 2014), which may reflect evolutionary differences between Zeb2 and Zfh1. Interestingly, conditional knockout of Zeb2 in the MGE resulted in upregulation of Cited1 (McKinsey et al, 2013), a transcriptional coactivator which promotes Smad-p300 interaction (Gerstner and Landry, 2007;Yahata et al, 2000), suggesting that Zeb2 and Cited1 may act antagonistically during MGE development.…”
Section: Zeb2 In Cerebral Developmentmentioning
confidence: 99%
“…Additional effectors of Eve likely ensure that dorsal motor axons reach their target muscles, as the strongest phenotype produced by triple unc-5, beat1a and nrg mutants does not recapitulate the effect of loss of eve. Nevertheless, by demonstrating a functional connection between upstream regulatory factors and target genes, this study provides insight into how transcriptional regulators exert their activities through a battery of effectors (Zarin et al, 2014).…”
Section: Lim Homeodomain Transcription Factors and Their Effectors Inmentioning
confidence: 97%
“…A recent genome-wide study of mRNA isolated from FACssorted dorsally projecting motor neurons (d-MNs) identified additional downstream effectors of Eve (Zarin et al, 2014). Candidate targets include four cell-surface receptors of the immunoglobulin superfamily (IgSF): unc-5, beat1a (beaten path 1a), fasciclin 2 ( fas2) and neuroglian (nrg), all of which are positively regulated by Eve.…”
Section: Lim Homeodomain Transcription Factors and Their Effectors Inmentioning
confidence: 99%
See 1 more Smart Citation